Perception of airport users on environmental-friendly airport chair design in KLIA - Rusli, Asa Naim; Mohamed, Shukri (Faculty of Design & Architecture, Universiti Putra Malaysia, 2017)
Malaysia Airport Holding Berhad (MAHB) has taken several measures to spread environmental awareness among the staff and communities. Nevertheless, the awareness appeared to be lacking in the context of ecodesign product. Eco-design integrates multifaceted design aspects and reflects the environment concept. Understanding consumers’ needs and desires is imperative in designing environmental-friendly product. As consumers’ expectation plays an important role in developing eco-products, a survey was carried out to evaluate the user’ (passengers) environmental-friendly perception and eco-design attributes on the current airport chair use in KLIA. In KLIA, airport chairs appear to be the significant facility used by the passengers. The results indicated that the most users rated that the existing airport chair did not apply environmental-friendly practices. Users viewed on attributes characteristics for eco-design chair was categorized into physical appearance (i.e.- attraction feelings, design and colour), sensational feeling (i.e.- physical, health, and usability) and physical characteristics (recycle, reusable, eco-material, reduce cost and reduce environmental impact). Based from these findings, this study contributed towards integrating environmentalfriendly concept with users’ perception as part to promote sustainable product.